2001
DOI: 10.1302/0301-620x.83b5.11539
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty using porous-coated femoral components in patients with rheumatoid arthritis

Abstract: W e studied the results of total hip arthroplasty (THA) using AML porous-coated femoral components at a mean follow-up of 11 years in a non-selected, consecutive series of patients with rheumatoid arthritis. We reviewed 64 patients with 82 primary THAs using these components. There were seven men (8 hips) and 57 women (74 hips) with a mean age of 55.1 years (24 to 80) at the time of surgery.Nine patients (11 hips) died before the two-year follow-up. Of the remaining 71 hips, only one stem was revised for asept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…The 88% survival at 15 years found in this study shows that the Lord femoral component has a rather favourable outcome in RA compared with other stem types [13,16]. Jana et al published a series of 82 THAs with a uncemented, porous-coated, anatomical medullary locking stem [7] with a 10-year survival of 98.1%. The Bi-Metric cementless stem had a survival of 97.4% at 10 years in patients with juvenile chronic arthritis [16].…”
Section: Discussionmentioning
confidence: 62%
“…The 88% survival at 15 years found in this study shows that the Lord femoral component has a rather favourable outcome in RA compared with other stem types [13,16]. Jana et al published a series of 82 THAs with a uncemented, porous-coated, anatomical medullary locking stem [7] with a 10-year survival of 98.1%. The Bi-Metric cementless stem had a survival of 97.4% at 10 years in patients with juvenile chronic arthritis [16].…”
Section: Discussionmentioning
confidence: 62%
“…L'âge et la polyarthrite ne semblent pas une contre-indication à l'utilisation d'une prothèse sans ciment dans la littérature, sur l'un, l'autre ou les deux versants de la prothèse de hanche [3], même si la plupart des publications font état de prothèses cimentées. Les polyarthritiques ont deux fois plus de risque de luxer leur prothèse de hanche, précocement ou à grande distance, ce qui pourrait pousser à l'utilisation d'emblée de prothèses de hanche à double mobilité.…”
Section: Type De Prothèseunclassified
“…C'est très réguliè-rement entre 75 et 80 ans pour une prothèse totale de hanche [3,32], et nous voyons très régulièrement des patientes de plus de 80 ans en très bonne condition physique. Peut-être sera-t-on plus circonspect pour la réalisation d'une prothèse de genou, en raison des pertes sanguines postopératoires et du risque d'accident vasculaire cérébral, les plus petits se traduisant par une désorienta-tion postopératoire transitoire.…”
Section: Limites Liées à L'âge Et Au Terrainunclassified
“…Some (Unger et al 1987, Snorrason et al 1993, Lachiewicz 1997, Creighton et al 1998, Jana et al 2001, Tang and Chiu 2001) but not all authors (Kirk et al 1993, Ranawat 1998, Furnes et al 2001, Eskelinen et al 2006) have reported a poor prognosis of THA in RA patients, but the findings have been inconsistent. Several design issues may have undermined the existing study results, including small study samples, lack of long-term follow-up, incomplete follow-up, and lack of control groups (e.g.…”
Section: Introductionmentioning
confidence: 99%